Optimisation of peripheral visual function using stimulus-based manipulations - Patrick, Jonathan A. (2017)
Ocular disorders that restrict visual capacity in the centre of the visual field, such as age-related macular degeneration (AMD) and Stargardt’s disease, force patients to perform important visual tasks in the periphery. It is well documented that visual performance is progressively limited as the peripheral eccentricity at which the task is performed increases. Since many of the disorders that cause central vision loss currently have no cure, adaptive techniques to optimise the remaining visual function are required. This thesis describes a series of psychophysical experiments that aim to optimise stimulus perception using manipulations to the stimulus input. Super-resolution (SR) is a form of image processing wherein multiple low-resolution images are merged over time to form a higher-resolution image. In many situations, the low- resolution sequence of images is produced by motion. Because of this, the effect of motion on peripheral acuity is first examined. The benefit of motion on acuity observed within 10° in the healthy periphery was very limited to specific combinations of target speed and retinal location. Thus, the investigation was extended to artificially undersampled stimuli. Spatial undersampling was achieved by presenting stimuli behind partially opaque masks. A significant benefit of motion was identified for the partially occluded stimuli, indicating a SR mechanism that operates when the visual input is sufficiently undersampled. In further experiments, it was established that smooth motion, originating from the target, is a key condition required for peripheral SR to be most effective. Since motion was shown to be insufficient to significantly improve resolution in the typical periphery, the effects of additional temporal modulations applied to static and moving stimuli were examined. Applying periodic temporal modulations to stimuli has the effect of creating temporal harmonics of the stimulus in the Fourier domain. The purpose of these experiments was thus to examine whether the visual system is capable of utilising these harmonics to better resolve the target. Temporally subsampling the stimulus, such that it appears with blank temporal intervals, was shown to drastically reduce the motion-related loss of acuity. However, at low target speeds, resolution thresholds were higher in the more subsampled conditions. It was shown that the loss at low speeds was driven by a reduction in the time-averaged contrast that accompanies temporal subsampling. Next, the effect of contrast polarity reversal was examined, whereby the target switches between black and white at periodic intervals, thus preserving the time-averaged contrast. Contrast polarity reversal diminished the motion-related loss, while also providing an overall reduction in resolution thresholds across speeds. Certain temporal modulations may therefore improve peripheral acuity for static and moving targets. To test whether the benefit of temporal modulations may be of use in a patient population, the effect of modulating the stimulus on resolution thresholds was examined in simulated conditions of ocular disease. A common comorbid symptom of central vision loss is exaggerated ocular jitter. The effects of subsampling and contrast polarity reversal were examined on resolution thresholds for targets jittering in accordance with ocular motion, multiplied by a variable gain factor. Temporal subsampling, as for smooth motion, was a hindrance to resolution. Contrast polarity reversal, however, was shown to improve performance at all levels of jitter. Contrast polarity reversal was also examined in simulated conditions of neuro-retinal matrix disorder (NRMD), whereby targets appear with spatial undersampling. There was no significant improvement in resolution for undersampled targets. Thus, while temporal modulations may be beneficial in some central vision loss disorders, the results do not support its use in NRMD patients. Additional temporal stimulus modulations therefore have diverse effects on resolution. To investigate the mechanisms driving these effects, a model was created to examine how the temporal modulations were influencing the perception of the stimulus. In the development of the model, the spatiotemporal characteristics of the stimulus were assessed. By calculating the extent to which the stimulus was compromised of frequencies to which the visual system is sensitive, an estimate of how visible the target should be in each condition was estimated. In assessment of the spatiotemporal characteristics of the stimuli, it was confirmed that contrast alone is not sufficient to explain the benefits of contrast polarity reversal. Further, the model indicated that the extended spectral range additional temporal modulations provide the stimulus is a reasonable explanation of the effects the modulations have on resolution, when combined with a description of the retinal response to temporally modulating stimuli. Finally, to confirm the use of contrast polarity reversal as a technique to optimise peripheral function in vision loss disorders, it was examined in a more salient task for patients: peripheral reading. Reading speed and accuracy were assessed for peripheral sentences with and without temporal modulation, in healthy observers and in patients with central vision loss. Both healthy observers and patients made significantly fewer errors in the contrast polarity reversal conditions than in the unmodulated conditions. However, only the healthy observers demonstrated a reduction in reading speed. While the results do not wholly support contrast polarity reversal, it was postulated that patients with more severe symptoms of AMD may reveal a stronger benefit. Thus, the experiments in this thesis have demonstrated that performance on several peripheral visual tasks can be improved by applying additional temporal modulations to the stimulus. Further, it has been indicated that this benefit stems from a combination of the contrast of the stimulus, and the effect of the modulation on the spatiotemporal characteristics of the target.